1975
DOI: 10.1042/cs0490359
|View full text |Cite
|
Sign up to set email alerts
|

Defective Membrane Systems in Dystrophic Skeletal Muscle of the UM-X7.1 Strain of Genetically Myopathic Hamster

Abstract: 1. The function of mitochondria, sarcotubular membranes (heavy microsomes), sarcolemma and myofibrils from the hind-leg skeletal muscle of about 60- and 150-day-old normal and myopathic (UM-X7.1) hamsters was examined. 2. The mitochondrial calcium uptake as well as mitochondrial phosphorylation and respiratory rates were lower in 60-day-old myopathic skeletal muscle, unlike 150-day-old myopathic animals, when pyruvate-malate and glutamate-malate were used as substrates. However, mitochondria from 150-day-old m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…Ultrastructural examination of dystrophic muscle revealed segmental fiber breakdown and Ca 2+ -deposits in myocytes with intact basement membrane as significant features [65,66,[70][71][72]. Several changes indicating biochemical abnormalities in the sarcolemma (SL) membrane were observed in differ-ent types of dystrophic muscle [73][74][75][76]. Marked alterations in lipid and electrolyte content were also seen in dystrophic muscle indicating abnormal function of the cell for maintaining appropriate levels of intracellular components [73,77].…”
Section: Biochemical Defects In Dystrophic Musclementioning
confidence: 99%
See 2 more Smart Citations
“…Ultrastructural examination of dystrophic muscle revealed segmental fiber breakdown and Ca 2+ -deposits in myocytes with intact basement membrane as significant features [65,66,[70][71][72]. Several changes indicating biochemical abnormalities in the sarcolemma (SL) membrane were observed in differ-ent types of dystrophic muscle [73][74][75][76]. Marked alterations in lipid and electrolyte content were also seen in dystrophic muscle indicating abnormal function of the cell for maintaining appropriate levels of intracellular components [73,77].…”
Section: Biochemical Defects In Dystrophic Musclementioning
confidence: 99%
“…Alterations in the integrity of dystrophic muscle membrane [79,80] were associated with changes in different SL enzyme systems such as Na + -K + ATPase, Ca 2+ /Mg 2+ ecto-ATPase, and adenylyl cyclase [74][75][76][81][82][83][84][85]. Since both cholesterol and phospholipids are known to exert membrane stabilizing effects [86,87] and the ratio of cholesterol/phospholipids was elevated in dystrophic muscle [88], it has been suggested that the observed changes in enzyme activities are a consequence of alterations in the SL lipid composition.…”
Section: Biochemical Defects In Dystrophic Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Cardiomyopathy in hamsters develops in a phasic pattern with well-defined and predictable stages: 1, a necrotic phase with disseminated lesions in the myocardium elapsing between 30 and 120 days; 2, a healing phase characterized by a scarring process with ventricular hypertrophy and dilatation until 200 days of age; 3, a terminal phase with typical changes of heart failure until death occurs near 250 days (Dhalla et al 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in membrane function have been reported in dystrophic hamsters (Sulakhe et al, 1971;Mezon et al, 1974;Dhalla et al, 1975), as well as in dystrophic mice, in dystrophic chickens and in humans with Duchenne dystrophy (see, e.g., Mawatari et al, 1976';, Wrogemann & Pena, 1976; * To whom reprint requiiests should be addressed. Howland & Iyer, 1977;Duncan, 1978;de Kretser & Livett, 1977;Mrak & Baskin, 1978;Rodan et al, 1974;Sabbadini et al, 1975;Louie & Peck, 1979).…”
mentioning
confidence: 99%